Nosocomial Infections in Intensive Care Unit: Pattern of Antibiotic-resistance in Iranian Community - Esfahani, Bahram Nasr (Adv Biomed Res, 2017)
BACKGROUND: Bacterial infections are responsible for great number of mortality in Intensive Care Unit (ICU). Knowledge about prevalence of bacterial infections and their antibiotic-resistance pattern would be a great step for their treatment and management. MATERIALS AND METHODS: Data about nosocomial infections in ICUs of Alzahra Hospital (referral hospital in Isfahan, center of Iran) were gathered during the years 2007–2010. A questionnaire was fulfilled for any specific patient with nosocomial infection containing demographic data of patient and also characteristics of the infection. RESULTS: Out of all patients, 707 individuals (65.6%) were male and 370 (34.4%) were female. Our data revealed that Pseudomonas aeruginosa (13.9%), Klebsiella (11%), and Escherichia coli (6.4%) were the most prevalent bacterial infections. The most common sites of nosocomial infections in the ICU were respiratory system (399 cases, 37%), urinary system (230 cases, 21.4%), and blood (102 cases, 9.5%). The antibiotic-resistance of each bacteria in ICU ward was assessed and data were categorized in a table. There were less documentary about bacterial cultures in the year 2007 when compared with the next years. CONCLUSION: We found some differences (such as bacterial prevalence in ICU wards which caused nosocomial infections) in our local prevalence of nosocomial infections and also in their resistance pattern compared to other centers. Knowing about our data will help physicians to administer the most suitable antibiotics for treatment of nosocomial infections in our area.